2017
DOI: 10.1136/bmjopen-2016-015497
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of redactions in Canada’s Common Drug Review Clinical Review Reports and how they relate to the patients’ voice

Abstract: ImportanceCanada’s Common Drug Review (CDR) evaluates drug data from published and unpublished research, as well as input from patient groups, to recommend provincial coverage. Currently, the CDR process gives manufacturers the opportunity to redact information in the final publicly available report. Patients often have strong feelings regarding the efficacy, harms, health-related quality of life (HRQL), and cost associated with the drugs under review and their redacted data. Highlighting Canada’s approach wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[52] Among these, the patients’ voice and the opinion of the patient group should be given more consideration than is typically the case. [53] Based on the research results, regardless of whether or not the opinions of the patient group or the industry on weights were considered, the final research results remained unaffected. Even so, diverse opinions should make it possible to arrive at more objective, consistent answers.…”
Section: Discussionmentioning
confidence: 99%
“…[52] Among these, the patients’ voice and the opinion of the patient group should be given more consideration than is typically the case. [53] Based on the research results, regardless of whether or not the opinions of the patient group or the industry on weights were considered, the final research results remained unaffected. Even so, diverse opinions should make it possible to arrive at more objective, consistent answers.…”
Section: Discussionmentioning
confidence: 99%
“…Any product with biologic components was coded as biological agent. These definitions have been previously published [4].…”
Section: Methodsmentioning
confidence: 99%
“…Patient-centered care, shared decision making and evidence based medicine are becoming widely used practices; however, they require objective, unbiased research to be publicly accessible [4]. Wieseler et al [5] found a substantial number of patient-relevant outcomes were missing from the public record, making unbiased trial evaluation challenging.…”
Section: Introductionmentioning
confidence: 99%